1996
DOI: 10.1088/0953-4075/29/22/003
|View full text |Cite
|
Sign up to set email alerts
|

Electron impact excitation out of the metastable levels of argon into the level

Abstract: We have measured the direct cross section for electron impact excitation out of the metastable 3p 5 4s[ 3 2 ] o 2 level (1s 5 in Paschen's notation) into the 3p 5 4p[ 5 2 ] 3 level (2p 9 ) of argon from threshold to 800 eV. The direct cross section is 40 × 10 −16 cm 2 at 10 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 12 publications
2
15
1
Order By: Relevance
“…The present results for the 2p 9 level differ from our earlier results reported in Ref. [18]. The earlier work used the ground state cross sections of Ballou et al [20] for absolute calibration, and these cross sections were not fully corrected for pressure effects.…”
contrasting
confidence: 89%
See 2 more Smart Citations
“…The present results for the 2p 9 level differ from our earlier results reported in Ref. [18]. The earlier work used the ground state cross sections of Ballou et al [20] for absolute calibration, and these cross sections were not fully corrected for pressure effects.…”
contrasting
confidence: 89%
“…Emissions arising from 2p atoms populated by cascades will have a different temporal (and thus spatial) pattern than emissions from 2p atoms populated by direct excitation, enabling us to estimate the cascade contribution to the fluorescence. Using this technique, we have previously shown that the cascade cross section for the 2p 9 level is much less than 20% of the apparent cross section [18]. We have now carried out similar measurements for the 2p 6 level and have found that the cascade cross section is less than 10% of the apparent cross section.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The consideration of electron-impact excitation cross sections for neon and xenon both from the ground state and their metastable levels [12] together with the evolution of the amplitude of the current allow for a schematic description of the main kinetic reactions involved in the plasma species temporal evolution and the evolution in the electronic temperature during the pulse excitation. At the pulse onset, the plasma from the previous pulse is largely recombined, the tube impedance is high, in the kOhm range, the electronic density is low and the electronic temperature is high which is favourable for the direct excitation of the xenon and neon excited levels from their respective ground states.…”
Section: Pulsed Neon Xenon Plasma Kineticsmentioning
confidence: 99%
“…Then as the current density increases, the positive column plasma is established, the typical electronic temperature is around 1 eV, and the main electron impact reactions involve electrons having energies of a few eV. These plasma parameters are very favourable for stepwise excitation and ionization in the case of xenon and stepwise excitation for neon [12]. The spectroscopic analysis reveals indeed the decrease of all the observed xenon transitions and the large increase of all the neon transitions during the second stage of the glow phase.…”
Section: Pulsed Neon Xenon Plasma Kineticsmentioning
confidence: 99%